Multiscale Analysis on the Behaviour of a Lime Treated Bentonite. (2016) - Vitale, Enza; Deneele, Dimitri; Russo, Giacomo
Abstract: An insight into the microstructural evolution of clay-lime-water systems and its influence on the hydro-mechanical behaviour of treated bentonite has been presented. The time-dependent mineralogical and microstructural changes induced by lime addition on a natural bentonite have been investigated in order to provide a better understanding of the kinetic of the ongoing reactions. The effects of lime addition on the clay particle arrangements have been inferred from dynamic light scattering measurements, whereas the mineralogical changes have been monitored at increasing curing time by X-Ray diffraction and thermogravimetric analysis. The bentonite showed a high initial reactivity characterized by a rapid and total consumption of lime, which promoted the formation of new hydrated phases since the very short term (0 days of curing). Oedometer tests on not treated and lime stabilised saturated samples have been performed at increasing curing times. The results showed the combined effect of clay particles arrangement and bonding on the mechanical behaviour of treated samples.